Evaluating the Long-Term Durability of Lime Treatment in Hydraulic Structures: Case Study on the Friant-Kern Canal. Issue 6 (June 2020) - Akula, Pavan; Hariharan, Narain; Little, Dallas N.; Lesueur, Didier; Herrier, Gontran
The slopes along the Friant-Kern Canal were last treated in the 1970s with 4% quick lime to mitigate issues related to slope failure caused by expansive Porterville soils. The immediate benefits of lime treatment were well documented by the Bureau of Reclamation. However, questions remain over the long-term durability of lime-treated materials. In this study, we compare the engineering properties and changes in the soil mineralogy of treated and untreated sections to establish the effectiveness of lime after more than 40 years of performance. A geochemical model was developed using the GEM-Selektor program to simulate the geochemical reactions in the soil-lime system and predict stable pozzolanic products. The experimental results show a reduction in the plasticity index from 23 to 6 after lime treatment together with a tenfold increase in strength. Lime addition lowers the risk of volumetric expansion and erosion in soils from moderately high to very low. Further, a pH increase from 6.30 to 8.90 in lime-treated sections indicates that lime treatment continues to be effective. X-ray fluorescence analysis shows the presence of Ca 2+ ions in quantities similar to the initial treatment dosage indicating negligible leaching of lime. The geochemical model provides evidence of the formation of pozzolanic products in the soil-lime system which was validated using thermogravimetry analysis. The performance history of the Friant-Kern Canal together with the findings of this study affirm the long-term durability of lime treatment on this project and strengthens the case for using lime in the repair of hydraulic structures.